2015
DOI: 10.1007/978-3-319-22348-3_13
|View full text |Cite
|
Sign up to set email alerts
|

ValueApping: An Analysis Method to Identify Value-Adding Mobile Enterprise Apps in Business Processes

Abstract: Mobile enterprise apps provide novel possibilities for the optimization and redesign of business processes, e.g., by the elimination of paper-based data acquisitioning or ubiquitous access to up-to-date information. To leverage these business potentials, a critical success factor is the identification and evaluation of value-adding MEAs based on an analysis of the business process. For this purpose, we present ValueApping, a systematic analysis method to identify usage scenarios for value-adding mobile enterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The advancement of mobile technologies and the resultant rise in the use of mobile applications (apps) over the past decade has resulted in the ubiquitous use of these technologies (Hasan, Gómez, & Kurzhöfer, 2013;Hoos, Gröger, Kramer, & Mitschang, 2015). Other evidence of this shift in mobile technology adoption is that mobile traffic was set to grow to 52% of all website traffic in 2018, up from 50.3% in 2017 (Statisa, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of mobile technologies and the resultant rise in the use of mobile applications (apps) over the past decade has resulted in the ubiquitous use of these technologies (Hasan, Gómez, & Kurzhöfer, 2013;Hoos, Gröger, Kramer, & Mitschang, 2015). Other evidence of this shift in mobile technology adoption is that mobile traffic was set to grow to 52% of all website traffic in 2018, up from 50.3% in 2017 (Statisa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps used in business are called mobile enterprise apps (MEAs), and they are one of the top ten strategic technology trends since 2014 (Hoos et al, 2015). Market research in 2016 showed that 35% of employees used apps for work-related activity (Gartner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the longlists of digital technologies and sub-processes to medium lists does not require a special tool, but depends on organization-specific considerations. For some digital technologies (e.g., mobile enterprise apps or knowledge management systems), there already are methods users can use to complement, support, or affirm the outcome of our method (Hoos et al 2015;Greco et al 2013). Note that some of these methods require more information than initially provided from a behavioral process perspective to be applied.…”
Section: Activity 2: Preselection Of Suitable Digital Technologiesmentioning
confidence: 99%
“…For this purpose, the DIPPing app was designed specifically to be available on mobile devices and to generate and display DIPs by using the previously introduced architecture. To evaluate if it is benefical to use mobile devices, we performed the ValueApping Method [22]. Consequently, the goal of the DIPPing app is composed of the following sub-goals:…”
Section: Goalmentioning
confidence: 99%